The Effect of Change Management, Organizational Culture, and Internal Communication on Employee Performance with Change Readiness as a Mediating Variable at PT Angkasa Pura Indonesia Belitung Branch - Abdul Halim; Herry Achmad Buchory (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of change management, organizational culture, and internal communication on employee performance with change readiness as a mediating variable at PT Angkasa Pura Indonesia, Belitung Branch. The research method applied was descriptive-verificative with a quantitative approach. Data were collected through questionnaires distributed to employees and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results indicate that change management and internal communication have a positive and significant effect on change readiness, while organizational culture does not show a significant effect. Furthermore, change management, organizational culture, and internal communication do not have a direct impact on employee performance. However, change readiness has been proven to positively and significantly influence employee performance. In addition, change readiness mediates the relationship between change management and internal communication on performance, but does not mediate the effect of organizational culture on performance. These findings emphasize that change readiness is a crucial factor in improving employee performance during organizational transformation. The practical implications of this research can be utilized by the management of PT Angkasa Pura Indonesia, Belitung Branch, to strengthen change management strategies, enhance the quality of internal communication, and build employee readiness in facing organizational dynamics, thereby optimizing performance improvement.